2021
DOI: 10.1016/j.psj.2021.101206
|View full text |Cite
|
Sign up to set email alerts
|

On-site generated peroxy acetic acid (PAA) technology reduces Salmonella and Campylobacter on chicken wings

Abstract: Peroxyacetic acid ( PAA ) is a widely used antimicrobial during poultry processing that requires to be shipped in a concentrated solution, stored under hazardous conditions and diluted for use. On-site PAA generation using nonhazardous ingredients can help eliminate transportation and storage issues at the processing plant and reduce the risk of occupational hazards. The objective of the proposed research was to 1) evaluate the efficacy of on-site generated PAA in reducing Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The greater effectiveness of PAA seen in this meta-analysis compared with chlorine could be due to several factors. First, changes in pH have less of an influence on the effectiveness of PAA than on chlorine ( Kataria et al, 2020 ; Vaddu et al, 2021a , b ). This is useful because poultry processors prefer using higher pH values in the primary chiller (≥8.0 pH) to prevent moisture loss from carcasses and to improve carcass yields ( Vaddu et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The greater effectiveness of PAA seen in this meta-analysis compared with chlorine could be due to several factors. First, changes in pH have less of an influence on the effectiveness of PAA than on chlorine ( Kataria et al, 2020 ; Vaddu et al, 2021a , b ). This is useful because poultry processors prefer using higher pH values in the primary chiller (≥8.0 pH) to prevent moisture loss from carcasses and to improve carcass yields ( Vaddu et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors argued that the surface to which pathogens were attached as affected by temperature (chilled vs. hot carcass surface) might have a significant effect on the efficacy of PAA. Nonetheless, over the past few decades, the activities of PAA on food-borne pathogens have been observed to be highly effective [20,22,36,37]. Bauermeister et al (2008) [20] tested different concentrations of PAA on poultry carcasses and observed that as little as 25 ppm of PAA could reduce Salmonella spp.…”
Section: Peroxide-based Compoundsmentioning
confidence: 99%
“…However, these results should be validating in an industrial plant. It is necessary a method that measures the concentration of PAA in the post-cooling tank while the carcasses are being immersed successively, as well as the stability of the chemical agent (PAA) (Vaddu et al, 2021) in a real application. Besides that, must be tested the possible toxic effects of formulation (use of stabilizers such as HEDP) on the food and the environment.…”
Section: Effect Of Treatment 007% Paa In Crosscontaminationmentioning
confidence: 99%